2004
DOI: 10.1097/00008390-200412000-00003
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutations are detectable in conjunctival but not uveal melanomas

Abstract: Activating mutations in exon 15 of BRAF have been detected in a high proportion of cutaneous melanomas. To determine whether such mutations are a feature of conjunctival or uveal melanomas, we screened DNA from these tumours. Twenty-one conjunctival and 88 uveal tumours were included in the study. Mutation analysis of BRAF exons 11 and 15 was undertaken using a combination of conformationally sensitive gel electrophoresis and direct sequencing. Mutations in exon 15 were detected in three of the conjunctival tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 20 publications
4
69
0
Order By: Relevance
“…These mutations have been shown to be present in 66 to 80% of cutaneous melanomas and have also been detected in up to 82% of melanocytic nevi (Pollock et al, 2003). The mutation has also been reported in 22-40% of conjunctival melanomas and recently our group has identified this mutation in 48% of 19 iris melanomas (Gear et al, 2004;Spendlove et al, 2004;Henriquez et al, 2007). However, there have been several studies, in uveal melanoma including primary and metastatic choroidal and ciliary body melanomas and the BRAF mutation has only been identified in one case (Malaponte et al, 2006).…”
Section: Discussionmentioning
confidence: 75%
“…These mutations have been shown to be present in 66 to 80% of cutaneous melanomas and have also been detected in up to 82% of melanocytic nevi (Pollock et al, 2003). The mutation has also been reported in 22-40% of conjunctival melanomas and recently our group has identified this mutation in 48% of 19 iris melanomas (Gear et al, 2004;Spendlove et al, 2004;Henriquez et al, 2007). However, there have been several studies, in uveal melanoma including primary and metastatic choroidal and ciliary body melanomas and the BRAF mutation has only been identified in one case (Malaponte et al, 2006).…”
Section: Discussionmentioning
confidence: 75%
“…The majority of cutaneous melanomas occur in areas exposed to sun radiation, whereas the majority of uveal melanomas occur in the posterior segment of the eye, which is not exposed to significant sun radiation. Chromosomal assessment and molecular biological and epidemiological studies demonstrate that cutaneous melanomas differ from uveal melanomas (29)(30)(31)(32)(33)(34), whereas conjunctival melanomas appear to have more similarities to cutaneous than uveal melanomas (32,34). The primary underlying biological differences between uveal and cutaneous melanomas may be associated with various gene mutations and differing microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…1,23,25,27,42 Genetic abnormalities of CoM CoMs show mutation of BRAF (7q34). 45,46,[49][50][51][52]55 This gene encodes a serine/threonine kinase in the 45 We now test all CoMs routinely for the BRAF V600E mutation, which may predict responsiveness to Vemurafenib should the patient develop metastatic disease. 56 We have also demonstrated that primary CoM showed amplification of CDKN1A and RUNX2 (both 6p21.2); in metastatic CoM, MLH1 (3p22.1) and TIMP2 (17q25.3) were frequently amplified, and MGMT (20q26.3) and ECHS1 (10q26.3) were frequently deleted.…”
Section: Prognosismentioning
confidence: 99%